Integrating genetic and immune profiles for personalized immunotherapy in Alzheimer’s disease - He, Cong; Shen, Yiwei; Zhang, Miao; Zhou, Xiaoqing (Frontiers in Medicine, 2025)
Alzheimer’s disease (AD) is the most frequent cause of dementia worldwide, and it is estimated that the number of patients will increase to 131 million by 2050. Most of the current methods of dealing with AD are designed to alleviate the symptoms, and there is no effective way of stopping the progression of the disease. Personalized immunotherapy has the potential to be highly effective and cut down on side effects because it can be targeted accurately and intervened early. Considering the genetic factors, many studies are increasingly looking at taking the immune status into account. This article further discusses the genetic and immune characteristics of AD, the methods of integrating multiple histological data, the identification of biomarkers, the stratification of patients, the precise treatment plans, and the application and future trends of immunotherapy, giving new directions for the future treatment of AD. In this mini-review, the authors address the critical role that genetic background and immune status play in shaping therapeutic strategies for AD, noting that there is a unique immune response in carriers of the APOEε4 allele compared to non-carriers, and that this difference may affect the course of the disease as well as the efficacy of immunotherapy. The aim of this review is to give an overview of the current understanding of the influence of genetic and immune factors on each other in AD, focusing on the impact of the APOEε4 allele on the immune response and its implications for immunotherapy.